Epidemiological and therapeutic studies on sheep lice in Sayint district, South Wollo Zone, Northeast Ethiopia - Legesse, Simegn; Hailemelekot, Mussie; Tamrat, Habtamu; Alemu, Yeshwas F. (Frontiers in Veterinary Science, 2022)
An epidemiological (cross-sectional) and therapeutic (randomized controlled field trial) study was conducted on sheep lice in Sayint district, South Wollo, Northeast Ethiopia. The aim of the study was to (i) quantify the magnitude of sheep lice burden and the prevailing lice species, (ii) identify and quantify risk factors affecting lice infestation in sheep, and (iii) evaluate the efficacy of commonly used acaricides (diazinon and ivermectin) against sheep lice infestation. A total of 232 randomly selected sheep, 15 naturally infested sheep, and 80 viable Bovicola ovis lice were used for epidemiological, in vivo, and in vitro based therapeutic studies, respectively. Three naturally infested treatment groups each with five sheep (Group I—treated with diazinon, Group II—treated with ivermectin, and Group III—untreated/control) were used for in vivo therapeutic study. Lice count for the corresponding treatment groups was conducted on weekly basis using clinical and parasitological examinations. We used logistic regression to quantify the association between different putative risk factors and lice infestation, and the independent t-test and one-way ANOVA to compare the within and between treatment group mean lice count variations. The overall prevalence of sheep lice in the study area was 48.3%, where Bovicola ovis (83%) was the dominant lice species. Hair length, body condition, agroecology, and season were significantly (P < 0.05) associated with sheep lice infestation. Analysis of variance revealed that mean lice count significantly (P < 0.05) varies between treatment groups. A significant (P < 0.05) low mean lice cunt was recorded in diazinon- and ivermectin-treated groups when compared to untreated group. The in vivo efficacy of ivermectin (81%) was lower than diazinon (99%) when compared to the efficacy standard limit (98–100%). However, no significant mean lice count variation was recorded between the two groups. In vivo (99%) and in vitro (95%) assay evidence revealed that diazinon was highly effective for the treatment of sheep lice. According to this study, it can be concluded that the magnitude of sheep lice burden in Sayint district was found to be high and this could have a potential negative impact on sheep productivity and health performances. Thus, applying an appropriate intervention measure including the right choice of effective acaricides could help to control sheep lice in the study area.